Can fellow moderate the factors which influence impulsive buying in generation Z? - Listya, Khanti; Siahaan, Sondang Beatrix; Pane, Ira (Trigin Publisher, 2025)
Generation Z (Gen Z) is characterized by their comfort with technology, which they integrate into various daily activities like communication, education, entertainment, and online shopping. This technological immersion contributes to a more consumerist mindset among Gen Z when engaging in digital transactions, often leading to impulsive buying. Key elements driving this impulsive online behavior include lifestyle choices, promotional offers, and personal self-control. Additionally, societal and environmental pressures can encourage frequent online shopping for Gen Z, suggesting that peer influence might intensify the impact of lifestyle, promotions, and self-control on impulsive purchases. Various studies show that lifestyle, promotion, and self-control each influence impulsive buying, yet it remains unclear whether these variables simultaneously affect impulsive buying and whether peer influence serves as a determining factor in this relationship, particularly among Generation Z in Medan City. This study, conducted in Medan City, aimed to quantitatively assess how lifestyle, promotions, and self-control affect impulsive buying, with peer influence considered as a potential moderating factor. The research utilized a questionnaire as its primary tool, which was validated and found reliable through data quality and statistical tests. The linear regression analysis confirmed that lifestyle, promotions, and self-control each significantly impact impulsive buying. However, the analysis also revealed that peer influence does not act as a moderating variable for the effects of lifestyle, promotions, or self-control on impulsive buying.